The polyclad fauna (Platyhelminthes, Rhabditophora) of the Sinop Peninsula (Black Sea, Turkey) with the description of a new species of Cryptocelis Lang, 1884 - GAMMOUDI, MEHREZ; BULNES, VERONICA N.; KURT, GÜLEY (Mediterranean Marine Science, 2021)
Between October 2013 and July 2014, 40 polyclad specimens were collected during the systematic sampling of mussel beds along the coast of the Sinop Peninsula (Western Black Sea). Six species were identified, including a new Cryptocelis species. Cryptocelis sinopae sp. nov. is characterized by possessing a prostatic vesicle lined with a ridged fold in its anterior end and the presence of two secretory glandular folds in the distal dorsal wall of male atrium. Additionally, new records of Echinoplana celerrima Haswell, 1907 and Leptoplana mediterranea (Bock, 1913) are reported for the Black Sea and Turkey; and Leptoplana tremellaris (Müller OF, 1774) and Prosthiostomum siphunculus Delle Chiaje, 1822 for the coast of the Black Sea of Turkey. A short description of the reproductive behaviour of Pleioplana okusi Bulnes, Kalkan and Karahan, 2009 and Cryptocelis sinopae sp. nov. will be also provided.